Hubungan kompensasi CEO terhadap manajemen laba: Apakah kondisi pandemi Covid-19 ikut memengaruhi? - Yulius Jogi Christiawan; Elizabeth Jessica; Vania Nanda Djaja (Universitas Hayam Wuruk Perbanas, 2021)
The relationship between CEO compensation and earnings management has been studied by the researchers since Healy’s research in 1985. In its development, there are many conditions that can affect this relationship. One of the conditions is the condition of the Covid-19 pandemic. This Co-vid-19 pandemic has a significant role in the economic downturn, which in turn, it could affect the company’s profit target. Profits that do not reach the target may lead the CEOs to do earnings management. This study is aimed to determine the effect of the Covid-19 pandemic on the relationship between CEO compensation and earnings management. Earnings management is measured using discretionary accrual proxy with Modified Jones Model. The study was done on 217 non-financial companies listed in Indonesia Stock Exchange (IDX) in 2019 and 2020. The data analysis technique utilized panel data regression with the program GRETL. This study proved that the more compensation the CEOs receive, the less inclined they are to do earnings management. However, during the Covid-19 pandemic, this relationship tends to weaken, meaning that the CEOs would be more willing to manage earnings. The result of this study is expected to help shareholders in deciding CEO compensation in the midst of a pandemic situation.